How personalized and effective is immersive virtual reality in education? A systematic literature review for the last decade - Marougkas, Andreas; Troussas, Christos; Krouska, Akrivi; Sgouropoulou, Cleo (Multimedia tools and applications, 2024)
During the last decade, there has been a substantial increase of interest in studies related to Virtual Reality (VR) as a learning tool. This paper presents a systematic literature review of personalization strategies utilized in immersive VR for educational objectives in the classroom. For the purposes of this review, 69 studies between 2012 and 2022 were analyzed in terms of their benefits, limitations and development features. The novelty of the study mainly arises from the in-depth analysis and reporting of personalization strategies as well as gamification techniques used in VR applications. The significance of this research lies in the observation that earlier studies’ applications did not sufficiently incorporate adaptive learning content, indicating the necessity for more research in this field and revealing a research gap. In conclusion, as it encourages future research of this field, this study may be a beneficial reference for those interested in researching the implementation of Virtual Reality in education, including academics, students, and professionals.